2012
DOI: 10.7732/kjpr.2012.25.4.498
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Pyrus serotina Fruit in Different Cultivars and Parts

Abstract: -The aim of this study is to compare the total polyphenol, total flavonoid, and antioxidative activity among 5 cultivars of Korean pears cultivated in Korea. As a result of the analysis for the phenolic substance of 5 cultivars, such as Wonwhang, Sunwhang, Whangkeumbae, Chuwhang, and Shingo, the content of total polyphenol was higher in Shingo and Chuwhang, and the content of total flavonoid showed higher levels in Wonwhang and Sunwhang. In addition, this study found that DPPH radical-scavenging ability was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…Efficient substance of pomegranate for antioxidation was observed in the peels (Roh et al, 2005), and in a study on the antioxidant activity of Codonopsis lanceolate, the highest antioxidant activity was observed in the peels (Kang, 2009). However, according to the reports of Park et al (2007) on the measurement of the antioxidant activity observed in ethanol extracts from Korean pears varieties, the antioxidant activityfrom whole fruits and flesh + peel were higher than those measured from the peel, which are different from the results reported by Jin and Song (2012), where the antioxidant activity in the peel was higher than in the flesh. The other study showed that free radical scavenging activity increased as the concentration of the extract from litchi peels increased (Jeong et al, 2010), and free radical scavenging activity of the extracts from Campbell grape seeds and peels increased along with the extract temperature .…”
Section: Discussioncontrasting
confidence: 56%
“…Efficient substance of pomegranate for antioxidation was observed in the peels (Roh et al, 2005), and in a study on the antioxidant activity of Codonopsis lanceolate, the highest antioxidant activity was observed in the peels (Kang, 2009). However, according to the reports of Park et al (2007) on the measurement of the antioxidant activity observed in ethanol extracts from Korean pears varieties, the antioxidant activityfrom whole fruits and flesh + peel were higher than those measured from the peel, which are different from the results reported by Jin and Song (2012), where the antioxidant activity in the peel was higher than in the flesh. The other study showed that free radical scavenging activity increased as the concentration of the extract from litchi peels increased (Jeong et al, 2010), and free radical scavenging activity of the extracts from Campbell grape seeds and peels increased along with the extract temperature .…”
Section: Discussioncontrasting
confidence: 56%
“…The difference in composition of persimmon fruit must be due to the cultivar variation (Moghaddama et al, 2013;Mratinic et al, 2011;Jin and Song, 2012). Vitamin C content in the cultivar Hachiya grown in Turkey was 12 ㎎ 100/g of fruit (Celik and Ercisli, 2008).…”
Section: Discussionmentioning
confidence: 99%